Exploring the Reconciliation of Cultural Data on Wikidata: experiment applied with the museum collection of the National Historical Museum - Rosa Oliveira, Luis Felipe (2020)
This study was developed from the perspective of the semantic web and the linked open data, focusing on the data reconciliation technique. It seeks to understand how the process of reconciling cultural data with Wikidata occurs through the programming of scripts in the Python language, with the aim of contributing to the understanding of how to apply a technique of semantic enrichment in cultural databases. As a methodology, the stages of the data reconciliation scripts development are described. And as results, the products of the scripts application are presented in the reconciliation of part of the data of National Historical Museum museological collection with the digital objects of Wikidata. It is concluded that the process of describing the scripts development allowed to better understand how data reconciliation occurs in cultural collections, and that more attention should be paid to the normalization of the collection data, and that this type of application expands the potential for networked socialization of knowledge.